PENGARUH EKSTRAK KUNYIT (CURCUMA LONGA) TERHADAP WAKTU PERDARAHAN PADA TIKUS GALUR WISTAR - Hanan, Nadiya; wibowo, ickman setoaji; Kusumawati, Irma; Anggraini, Galuh; haksajiwo, valentino (Universitas Baiturrahmah, 2024)
Introduction: The occurrence of bleeding is a common complication in surgical procedures. The body's intrinsic mechanism for stopping bleeding is known as hemostasis. However, uncontrolled bleeding during and after surgery can pose a significant challenge for surgeons. The use of Curcuma longa extract, which contains curcumin and tannin, has been shown to reduce bleeding time. Aim: The objective of this study is to investigate the effect of Curcuma longa extract on bleeding time in Wistar rats. Methods: An experimental study was conducted, incorporating a post-test-only control group design.A total of 24 male Wistar rats were divided into four groups: those administered tranexamic acid (positive control), distilled water (negative control), 50% concentration of Curcuma longa extract, and 100% concentration of Curcuma longa extract.Surgical incisions of 0.5 cm were made at the base of the rat's tail. The bleeding time was determined by allowing blood to drip onto Whatman paper for 30 seconds per box until the bleeding stopped. The bleeding time was then calculated by counting the number of boxes with blood spots and multiplying by 30 seconds.The data obtained were analysed using the Independent sample t-test and Post Hoc Least Significant Difference (LSD) test. Results: The study demonstrated that the bleeding time of 100% turmeric extract was shorter than the 50% concentration. Conclusion: The findings indicate that Curcuma longa extract at concentrations of 50% and 100% can effectively shorten the bleeding time in Wistar rats